NUTRITIONAL POTENTIAL OF CASSAVA PEELS ENSILED WITH MORINGA, GLIRICIDIA AND LEUCAENA LEAVES - Pius, Amoka (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The experiment was conducted to assess the proximate composition, mineral content, gross energy and antinutrients of cassava peels ensiled with Moringa, Gliricidia and Leucaena leaves. The crude protein for cassava peels ensiled with Moringaoleifera (CMO) was 20.32g100g-1, cassava peels ensiled with Leucaenaleucocepphala(CLL) was 23.17g100g-1 and cassava peels ensiled with Gliricidiasepium (CGS) was 22.23g100g-1.Â Ether extract values were 4.02g100g-1, 3.56g100g-1 and 3.20g100g-1 for CMO,CLL and CGS respectively. Ash content for cassava peels ensiled with Moringa, Leucaena and Gliricidiawere 4.26g100g-1, 3.80g100g-1 and 4.20g100g-1 respectively. The crude fibre ranged from 12.03g100g-1 in CLL to 12.56g100g-1 in CGS. In cassava peels ensiled with Moringa, Leucaena and Gliricidia leaves Na, K, Ca, Zn were the most abundant minerals in all the treatments.The tannin content varied from 0.20g100g-1 in CMO to 0.45g100g-1 in CGS. The phytic acid ranged from 10.12g100g-1 in CMO to 14.76g100g-1 in CGS. The phytic-phosphorus ranged from 2.85g100g-1 in CMO to 4.16gg100g-1 in CGS. The oxalate contents were 2.85g100g-1, 3.52g100g-1 and 4.16g100g-1 in CMO, CLL and CGS respectively. It is evident that cassava peels ensiled with Moringa, Leucaena and Gliricidia have great potentials for livestock animals and could be utilized as a source of supplementary feed for ruminant animals.